Comprehensive Analysis of Cell Cycle-Related Genes in Patients With Prostate Cancer - Liu, Zehua; Pan, Rongfang; Li, Wenxian; Li, Yanjiang (Frontiers in Oncology, 2022)
This study was performed to identify critical cell cycle related genes (CCRGs) that are differentially expressed in prostate cancer (PRAD) and to evaluate the prognostic values of selected gene panel. The gene set variation analysis (GSVA) of dysregulated genes among PRAD and normal tissues demonstrated that the cell cycle related pathways played vital role in PRAD. Moreover, according to the CCRGs, the patients could be classified into four clusters, which were associated with divergence recurrence free survival (RFS). Then 200 prognostic-related genes were selected using Kaplan–Meier (KM) survival analysis and univariable Cox regression with the threshold of KM < 0.05 and cox p-value < 0.05. By using random survival forest and multivariate regression cox method, the prognostic CCRGs risk score was constructed, and the efficiency was validated in MSKCC and GSE70770. Finally, we identified nine survival-related genes, CCNL2, CDCA5, KAT2A, CHTF18, SPC24, EME2, CDK5RAP3, CDC20 and PTTG1. Based on the median of risk score, the patients were divided into two groups. Then the functional enrichment analyzes, mutational profiles, immune components, estimated half maximal inhibitory concentration (IC50), and candidate drugs were conducted between different groups. In addition, the characteristic of nine hub CCRGs were explored in Oncomine, cBioprotal and the Human Protein Altas (HPA) datasets. Finally, the expression profiles of these hub CCRGs were validated in RWPE-1 and three PRAD cell lines (PC-3, C4-2 and DU-145). In conclusion, our study systematically explored the role of CCRGs in PRAD and constructed risk model that can predict the prognosis and immunotherapeutic benefits.